Description of three new species of Geometridae (Lepidoptera) using species delimitation in an integrative taxonomy approach for a cryptic species complex - Moraes, Simeão S.; Montebello, Ygor; Stanton, Mariana A.; Yamaguchi, Lydia Fumiko; Kato, Massuo J.; Freitas, André V.L. (PeerJ, 2021)
The genus Eois Hübner (Geometridae: Larentiinae) comprises 254 valid species, 217 of which were described from the Neotropics and 31 of those having their type locality in Brazil. Since this species rich genus has never been revised, and may potentially include many cryptic undescribed species, Eois embodies a problematic taxonomic scenario. The actual diversity of Eois is greatly underestimated and the Brazilian fauna is poorly known, both because of inadequate sampling and because of the potential existence of cryptic species "hidden" within some nominal taxa. In this study we investigated the diversity within a cryptic species complexes associated to the E. pallidicosta and E. odatis clades. We describe three new species Eois oya Moraes & Montebello sp. nov., Eois ewa Moraes & Stanton sp. nov., and Eois oxum Moraes & Freitas sp. nov., in an integrative taxonomy approach, using morphology, host plant use and species delimitation tools.
Keywords: Dna barcode; Cryptic species; Morphology; Taxonomy; Lepidoptera; Host-plant